PRAKTIK GADAI SAWAH DI DESA SIRNAJAYA RAJADESA MENURUT PERSPEKTIF EKONOMI SYARIAH - Aep Saepul Millah; Hasan Bisri (Fakultas Ekonomi dan Bisnis Islam, Institut Agama Islam Darussalam (IAID) Ciamis, Jawa Barat, INDONESIA, 2019)
This study aims to find out how the practice of pawning rice fields in the Sirnajaya Rajadesa village community and to find out how the sharia economic view of the practice of pawning rice fields in Sirnajaya Rajadesa Village. Data were collected through observation, interviews, documentation and literature study. There are two sources of data in this study, namely primary and secondary data sources. After the data has been collected, it is analyzed using the data reduction method, presenting the data and then drawing conclusions. The results showed that the practice of pawning rice fields by the people of Sirnajaya Rajadesa Village occurred due to urgent circumstances such as school needs, medical expenses and other needs. In the implementation of the agreement, it is carried out orally and there is no authentic (written) evidence that there has been a pledge agreement between the two. The practice of pawning carried out by the Sirnajaya Village community when viewed from the implementation of the contract has fulfilled the pillars and conditions of the pawn. However, judging from the economic principles and ethics, the practice of pawning fields carried out by the community is not in accordance with the Qur'an and Hadith.